Patient Perspectives on Outpatient versus Inpatient Cervical Ripening for Induction of Labor - Watters, Amber; Ekpe, Etoroabasi; Okafor, Annette; Donelan, Emily (American Journal of Perinatology, 2024)
Objective Our objective was to compare patient perceived control and experience with outpatient versus inpatient cervical ripening.Study Design This is a retrospective mixed-methods analysis of a quality improvement initiative focused on the impact to patients of incorporating outpatient cervical ripening into routine practice. Postpartum inpatients who had elected for outpatient cervical ripening (outpatients) and those who met criteria for outpatient cervical ripening but opted for an inpatient setting (inpatients) were invited to participate in the study. Patients completed the Perceived Control in Childbirth Scale, and scores were compared between outpatient and inpatient groups using Mann–Whitney U test. In addition, semistructured questions elicited feedback prior to hospital discharge, and these qualitative data were analyzed using iterative thematic analysis.Results The study population consisted of 36 outpatients and 38 inpatients. The median score on the Perceived Control in Childbirth Scale was 69 for outpatients and 67 for inpatients (p-value = 0.49), out of a maximum score of 72 (representing the highest level of perceived control). Both groups reported similarly high levels of perceived control, regardless of cervical ripening setting. In the qualitative analysis, pain was the most common theme in both groups. Inpatients reported more distress despite access to stronger pain medications. Outpatients utilized a variety of distraction techniques and expressed gratitude for their setting more than inpatients.Conclusion Outpatient cervical ripening can be a patient-centered solution to obstetric throughput challenges arising from increased numbers of inductions. Those who underwent outpatient cervical ripening had similar perceived control to those who underwent inpatient cervical ripening, suggesting that individual patient preferences are most important in determining the optimal setting for care. The patients' reported experiences identified focus areas for process improvement efforts and future research, including improving patient education regarding expectations and innovating new pain management strategies for cervical ripening.Key Points
Keywords: cervical ripening; labor induction; patient-centered care; quality improvement